A three-species synthetic community model whose rapid response to antagonism allows the study of higher-order dynamics and emergent properties in minutes - Aguilar-Salinas, Bernardo; Olmedo-Álvarez, Gabriela (Frontiers in Microbiology, 2023)
Microbial communities can be considered complex adaptive systems. Understanding how these systems arise from different components and how the dynamics of microbial interactions allow for species coexistence are fundamental questions in ecology. To address these questions, we built a three-strain synthetic community, called BARS (Bacillota A + S + R). Each strain in this community exhibits one of three ecological roles: Antagonistic, Sensitive, or Resistant, assigned in the context of a sediment community. We show that the BARS community reproduces features of complex communities and exhibits higher-order interaction (HOI) dynamics. In paired interactions, the majority of the S strain (Sutclifiella horikoshii 20a) population dies within five minutes when paired with the A strain Bacillus pumilus 145). However, an emergent property appears upon adding the third interactor, as antagonism of strain A over S is not observed in the presence of the R strain (Bacillus cereus 111). For the paired interaction, within the first five minutes, the surviving population of the S strain acquires tolerance to strain A, and strain A ceases antagonism. This qualitative change reflects endogenous dynamics leading to the expression for tolerance to an antagonistic substance. The stability reached in the triple interaction exhibits a nonlinear response, highly sensitive to the density of the R strain. In summary, our HOI model allows the study of the assembly dynamics of a three-species community and evaluating the immediate outcome within a 30 min frame. The BARS has features of a complex system where the paired interactions do not predict the community dynamics. The model is amenable to mechanistic dissection and to modeling how the parts integrate to achieve collective properties.